2020
DOI: 10.1038/s41598-020-59894-4
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin protects against cardiac cell death through reduction of ROS production and caspases activity

Abstract: fisetin treatment during the reoxygenation phase to mimic medication following surgery or dissolution of the thrombotic clot-our results are concordant. Our data also suggest that fisetin may have roles beyond cardiac protection, promoting cardiomyocyte proliferation and stimulating cardiomyocyte maturation. Further studies of cyclin-CDK complexes expression, degradation, phosphorylation activity and cellular localization would allow to better understand the effect of fisetin on cell cycle and DNA repair. Summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…These studies demonstrate the occurrence of crosstalk between the NLRP3 inflammasome and mtROS and suggest that targeting mtROS by the elimination of damaged mitochondria could be a promising therapeutic strategy for NLRP3 inflammasome-related immune disorders. Interestingly, a previous study demonstrated that fisetin prevents the generation of intracellular ROS in osteoclast differentiation [ 44 ] and cardiac cell death [ 45 ], indicating its antioxidative effects in various diseases. In this study, fisetin inhibited the LPS/ATP-induced activation of the NLRP3 inflammasome by inhibiting the depolarization of mitochondrial membrane potential and subsequent production of mtROS.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrate the occurrence of crosstalk between the NLRP3 inflammasome and mtROS and suggest that targeting mtROS by the elimination of damaged mitochondria could be a promising therapeutic strategy for NLRP3 inflammasome-related immune disorders. Interestingly, a previous study demonstrated that fisetin prevents the generation of intracellular ROS in osteoclast differentiation [ 44 ] and cardiac cell death [ 45 ], indicating its antioxidative effects in various diseases. In this study, fisetin inhibited the LPS/ATP-induced activation of the NLRP3 inflammasome by inhibiting the depolarization of mitochondrial membrane potential and subsequent production of mtROS.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a common condition in numerous cardiovascular events, such as ischemic heart disease, high altitude heart disease and cyanotic congenital heart disease ( 1 ). When subjected to hypoxia, cardiomyocytes develop disorders of mitochondria, membrane and lysosomes, leading to the initiation of the caspase cascade and activation of the Bcl-2 family ( 19 ). Oxidative stress and apoptosis are key mechanisms underlying hypoxia-induced injury ( 20 ) and are primary targets of Hyp ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also reduces ROS formation, activates caspases, protects from DNA damage, and ultimately inhibits apoptosis. Fisetin is a very promising drug for protection against ischemic damage after myocardial infarction and for counteracting ischemia reperfusion injury because it can, in addition, activate genes involved in cell proliferation [ 263 ].…”
Section: Pharmacological Therapeutic Possibilitiesmentioning
confidence: 99%